(3TQM JUQjas - (3GdJaJGRGfj, SYO GdOjf, eSYhO Hf YeQ Hf YHO Gddg, J(B793(3g`s
(3ChdgG (B:s
(3HSe Gddg(B...(3Ef CQhi RgQ JNQL aj QjGV GdcdGe ef GdEceGd, hCHgi MHQ JMGc HfjGf GdHjGf hCSfGf GdCbdGe MeO Gddg SHMGfg hJYGdi(B...(3hHYO ajbhd GdYHO GdabjQ Edi Gddg eSYhO Hf YeQ(B...(3deG QCjJ eNJUQ GdJUQja GdPj Ufag GdEeGe YHO GdhgGH Hf EHQGgje GdRfLGfj(B...(3eNJUQG jfWhs
(3BNQgG (B:s
(3abhdg(B: (3QMeJ QMeI hGMOI ddeQI hdWjaI hfMhgG ddfhY, hGfWdGbI hGMOI ddeQI hMSfI Ch bHjMI hZjQgG ddfhY cPdc GdHhGbj hGdMeO ddg Ydi GdEJeGes
(3jfJgj GdcJGH aj UaMI (B110(3, hJdjg ChQGb ef cJGH HBNQs
(3JHUQI GdeDda (B:s
(3aj eYLe GdeDdajf(B:(3J(B791(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B7(3,U(B219s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B849s
Keywords: (3GdUQas